How faculty with critical care specialties learn in a university hospital: a qualitative phenomenological study - Hyeyoon Jeong; Hyena Cho; Kyoung-Woo Seo; Janghoon Lee; Miran Kim; Jihye Yu (BMJ Open)
Objectives The study aims to explore the workplace learning experiences of medical faculty in critical care specialties at a university hospital, focusing on how they develop their professional identity and construct the meaning of their work.Design Qualitative, phenomenological study.Setting The current study was conducted at a university hospital in South Korea between November 2022 and October 2023.Participants Five faculty members (two males and three females) from critical care specialties (eg, emergency medicine) with over 15 years of experience, each having served as faculty at a university hospital for more than 5 years.Results Six key themes emerged: cultivating ‘doctor-ishness’ in the realm of critical care, beacon of inner drive: guiding professional growth, nexus for leveraging expertise and fostering professional growth, the challenging reality of becoming an ‘ideal’ faculty, the shifting tides of the medical profession’s role and weaving workplace learning into a unique rhythm of practice. These themes collectively highlight that faculty members’ workplace learning involves a transition from functional professionals to reflective practitioners.Conclusions Workplace learning of faculty members with critical care specialties is understood as an ongoing, context-dependent and individualised process in which emotions play a crucial role in determining the depth and significance of learning and shaping professional identities. This study highlights their capacity for agency and potential, offering a perspective beyond previous research that has primarily focused on their hardships. By shedding light on their workplace learning from an insider’s view and underscoring the need to support professional development in these high-stakes fields, our findings suggest theoretical and practical interventions to foster the mutual growth of faculty and hospital organisations.